Resolusi Konflik Perspektif Qur’an Al-Hujurat 13 Studi Analisis Konflik Antar Tetangga yang Berbeda Agama - Chairunnisah Zega; Hery Sahputra (CV. ALIM'SPUBLISHING, 2026)
Social conflict between neighbors is a phenomenon that often appears in pluralistic society and has the potential to disrupt social harmony if not managed constructively. The conflict is generally triggered by the lack of interfaith communication, social prejudice, socio-economic inequality, as well as external party provocations that utilize rift with social relations. This study aims to analyze the dynamics of conflict between neighbors are different religions and review the relevance of Q.S. Al-Hujurat paragraph 13 as theological runway in a resolution of conflict and a strengthening of plurality values. This study used qualitative methods with the approach of literature study (library research), through an analysis of the interpretation of the Qur'an, pluralism, and scientific literature relevant to the theme and resolution of conflict. The results show that Q.S. Al-Hujurat paragraph 13 emphasizes the principle of human equality, respect for diversity, and the concept of 'arafu (know each other) as the foundation of harmonious social interaction. Qur'ani values such as justice, tolerance, dialogue, patience, forgiveness, and help, are proven to be relevant as a conflict-based conflict resolution strategy (sulh). Implementation of this value through interfaith dialogue, multicultural education, and inclusive social policies are able to reduce prejudice and strengthen social solidarity. Thus, the integration of Q.S value. Al-Hujurat paragraph 13 in social life is a normative and practical approach to building a sustainable peace in the midst of a pluralistic society.